Penggunaan Bo’ Sangaji Kai sebagai Materi Ajar dalam Pembelajaran Sejarah Lokal di STKIP Yapis Dompu - Sumiyati Sumiyati; Husnul Khatimah; Enung Nurhasanah; Ririn Julianti; Desi Permatasari (Indonesian Journal of Social Science Education (IJSSE), 2023)
Teaching materials as one of the learning content have an important role for lecturers and students, teaching materials in UU No. 12 pasal 12 of 2012 concerning Higher Education explains that lecturers are obliged to write teaching materials or textbooks as a vehicle for learning resources for the development of academic culture. The local history course is one of the basic courses for students of the history education study program STKIP Yapis Dompu which requires an interesting learning approach and contains correct information. The sample of this research is STKIP Yapis Dompu history education students who have taken local history courses. The need for teaching materials for students is obtained through observation during learning with questionnaires and student responses are obtained through questionnaires which are then analyzed descriptively by percentage. A total of 70.21% of correspondents explained that teaching materials are needed to support student learning and understanding, besides that teaching materials should be able to help students to quickly understand the course, only 30.61% of correspondents find it difficult to understand the material in local History lectures with teaching materials that sourced from the notes of Bo' Sangaji Kai. Thus, teaching materials from Bo Sangaji Kai's notes as a learning resource have a very important role in the local history course Bima-Dompu in the history education study program of STKIP Yapis Dompu.